PENGARUH CITRA MEREK DAN PERSEPSI HARGA TERHADAP MINAT BELI (STUDI PADA FOLLOWERS INSTAGRAM ACCOUNT KAWAII COKELAT) - Chandra Arief, 15.05.51.0344; Sutejo, Bambang (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of brand image and price perception on buying interests of Instagram followers on the Kawaii Cokelat account. This research is a quantitative type that uses primary data. The technique of collecting data using a digital questionnaire (Google Form) is sent via Instagram direct messages (DM). Sampling is done by using purposive sampling method because respondents already have criteria.The results of the model test (F) have a value of 145,561 with a significance of 0,000 <0,05 so that the brand image variable and perceived price can be met together. The independent variable has a contribution of 0.712 which is listed on the value of adhjusted R². Hypothesis test results (t) brand image variables have a positive and significant influence with a t value of 10.261 and a significance of 0,000 <0.05 so that H1 is accepted, then the price perception variable has a positive and significant effect with a value of t count 3.597 and a significance level of 0,000 < 0.05 and on the value so H2 is requested to be accepted.